К изучению фауны совок Крыма. Сообщение VI. Группа Quadrifinae (Noctuidae, Lepidoptera) - Ключко, З.Ф. (Вестник зоологии, 1972)
The group Quadrifinae, the most ancient in the moth family, is phylogenetically presented in the Crimea by 83 species of eight subfamilies: Jaspidiinae — 13, Euteliinae — 2, Nycteolinae — 6, Pantheinae — 2, Plusiinae—13, Catocalinae—19, Othreinae—16, Hypeninae— 12. 37 species are marked for the Crimean peninsula for the first time, 4 species —.new for the Ukrainian fauna: P.orphyrinia griseola Ersch. , Mormonia neonympha E s p., Drasteria saisani S t g г., Hypena palpalis H b. The species of Mediterranean and Transipalaearctic complexes predominate.